(untitled) (Fiep Bulletin - online, 2015)
The congress in Istanbul will be the first big world congress in physical Education since the two lingiad-congresses in 1939 and 1949. By both of the latter great differences appeared concerning to attain the understanding of the methods to attain the goal for the work in Physical education in the school, a difference which made itself noticeable most acutely between the representation for the latin-speaking and the English- Speaking countries.